Synthesis and Characterisation of Vanadium Antimony Oxide Catalysts - Jong, Ita Yee Ping (2002)
V -Sb-oxide catalysts are commercially viable catalysts for the ammoxidation of propane to acrylonitrile, a novel and considerable cost saving route compared to the current industrial method which utilizes the ammoxidation of propene. The characteristic of VSb- oxide catalysts were studied and analyzed in relation to their structural/composition features using X-ray diffraction (XRD), Fourier Transform Infrared (FTIR), Brunauer- Emmett-Teller (BET) surface area, Scanning Electron Micrograph (SEM), Energy Dispersive X-ray (EDX) microanalysis and Thermogravimetric Analysis (TGA). Results showed significant difference in presence of crystalline phases, surface area, porosity and morphologies in the samples prepared according to three different methods, i.e. solid state (88) reaction, sol-gel (G8) and deposition on antimonic acid (DAA) methods, as a function of the Sb:V ratio and heat treatment. XRD and FTIR studies revealed that the calcination temperature at 500°C is not suitable for the V -Sb-oxide catalysts as there is little or no VSb04 formed in some samples. Sb/V ratio of2 or more is recommended for the GS method as there is hardly any Sb species formed for samples with 5bN ratio = 1. For the 55 method, sample calcined at 700°C with SbN ratio = 1 would be deemed the best as it has the highest amount of VSb04• Raising of calcination temperature had a detrimental effect on the surface area of the GS and DAA catalysts but bore no significant effect on SS catalysts. The EDX microanalysis showed antimony enrichment on the surface the catalysts. The study of TPD revealed the evolution of lattice oxygen from the catalysts. In TPR, the amount of oxygen desorbed from the catalysts prepared by SS method is found to be much higher compared to the other methods, i.e. about 16.7 times higher than GS method and 6.3 times higher than DAA method (for SbN = 1) whilst for ratio 3, it is 21.3 times higher than GS method and 14.5 times higher than DAA method.